2007
DOI: 10.1016/j.watres.2006.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous photodegradation and toxicity of the polycyclic aromatic hydrocarbons fluorene, dibenzofuran, and dibenzothiophene

Abstract: Decay kinetics resulting from the application of UV and UV/H 2 O 2 to the polycyclic aromatic hydrocarbons (PAHs) fluorene, dibenzofuran and dibenzothiophene was studied. Batch experiments were conducted with both low pressure monochromatic (253.7 nm) and medium pressure polychromatic (200-300 nm) UV sources alone or in the presence of up to 25 mg/L hydrogen peroxide, in a quasi-collimated beam apparatus. Degradation of all three PAHs, by both UV and UV/ H 2 O 2 , exhibited pseudo-first order reaction kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 33 publications
(31 reference statements)
1
38
0
1
Order By: Relevance
“…Although compared to the mixtures, much lower toxicity values were measured for DBF and FLU as sole components while, higher toxicity was found for DBT as a sole component [27]. Loibner et al [17] found additive bioluminescence inhibition effects to V. fischeri for low molecular weight PAHs acenaphthene (ACE), FLU, phenantherene (PHE), naphthalene, and acenaphthylene.…”
Section: Toxicitymentioning
confidence: 99%
“…Although compared to the mixtures, much lower toxicity values were measured for DBF and FLU as sole components while, higher toxicity was found for DBT as a sole component [27]. Loibner et al [17] found additive bioluminescence inhibition effects to V. fischeri for low molecular weight PAHs acenaphthene (ACE), FLU, phenantherene (PHE), naphthalene, and acenaphthylene.…”
Section: Toxicitymentioning
confidence: 99%
“…It is largely derived from anthropogenic products such as petroleum and coal tar, and natural processes such as forest fires. [6] It has a wide variety of uses as an insecticide, in the production of polyvinyl chloride (PVC), in industrial bleaching and incineration. Although it is known to be toxic, there is no information on the acute, chronic, reproductive, developmental and carcinogenic effects of DBF in humans or animals.…”
Section: Introductionmentioning
confidence: 99%
“…The AOPs can be used in treatment of different water matrices containing persistent harmful organic compounds with long environmental lifetime [11,12]. Polycyclic aromatic hydrocarbons (PAHs) have been detected in waste and natural waters [13]. The PAH compounds have been released into environment for example in wide use of creosote wood preservatives [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…The PAH compounds have been released into environment for example in wide use of creosote wood preservatives [9,14]. The organic portion of creosote consists mainly of the PAH compounds, many of which are considered to be toxic, carcinogenic and bioaccumulating [13]. Several studies have reported the usability of the UV/H 2 O 2 in the PAH decomposition but mainly from artificially contaminated wastewater [12,13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation